3-³ x (1/9)₋³
4⁻² x (1/16)⁻²
5⁻¹ X(1/125)⁻¹
6⁻² x (1/36)⁻²
(2/3)⁻² x (3/4)⁻²
(1 1/6)⁻³ x (3/7)⁻³
(2,8)⁻⁴ x (5/14)⁻⁴
(2,8)⁻⁴ x (5/14)⁻⁴
(5 1/3)⁻³ x (0,75)⁻³
3⁻² x 3₄
5² x 5⁻6
4-⁴ x 4²
2-⁸ x 2₅
(1 2/3)¹⁰ x (1 2/3)⁻⁸

3

Odpowiedzi

2009-11-21T16:04:09+01:00
1. 3-³ * (1/9)₋³ = 1/27 * 729 = 27
2. 4⁻² * (1/16)⁻² = 1/16 * 256 = 16
3. 5⁻¹ * (1/125)⁻¹ = 1/5 * 125 = 25
4. 6⁻² * (1/36)⁻² = 1/36 * 1296 = 36
5. (2/3)⁻² * (3/4)⁻² = 9/4 * 16/9 = 4
6. (1 1/6)⁻³ * (3/7)⁻³ = 216/343 * 3431/27 = 8
7. (2,8)⁻⁴ * (5/14)⁻⁴ = 1/16 * 1/16 = 1/256
8. (2,8)⁻⁴ * (5/14)⁻⁴ = 1/16 * 1/16 = 1/256
9. (5 1/3)⁻³ * (0,75)⁻³ = (16/3)-³ * (3/4)-³ = 1/64
10. 3⁻² * 3₄ = 3² = 9
11. 5² * 5⁻6 = 5-⁴ = 1/625
12. 4-⁴ * 4² = 4-² = 1/16
13. 2-⁸ * 2₅ = 2-³ = 1/8
14. (1 2/3)¹⁰ * (1 2/3)⁻⁸ = (1 2/3)² = (5/3)² = 25/9 = 2 7/9
2009-11-21T17:03:58+01:00
1. 3-³ * (1/9)₋³ = 1/3³ * 3⁶= 3³=27
2. 4⁻² * (1/16)⁻² = 1/16 * 256 = 16
3. 5⁻¹ * (1/125)⁻¹ = 1/5 * 125 = 25
4. 6⁻² * (1/36)⁻² = 1/6²* 6⁴ =6²= 36
5. (2/3)⁻² * (3/4)⁻² = 9/4 * 16/9 = 4
6. (1 1/6)⁻³ * (3/7)⁻³ = (7/6*3/7)⁻³=(1/2)⁻³=8
7. (2,8)⁻⁴ * (5/14)⁻⁴ = 1/16 * 1/16 = 1/256
8. to samo
9. (5 1/3)⁻³ * (0,75)⁻³ = (16/3*3/4)⁻³=4⁻³=1/64
10. 3⁻² * 3⁴= 3² = 9
11. 5² * 5⁻⁶ = 5-⁴ = 1/625
12. 4-⁴ * 4² = 4-² = 1/16
13. 2-⁸ * 2₅ = 2-³ = 1/8
14. (1 2/3)¹⁰ * (1 2/3)⁻⁸ = (1 2/3)² = (5/3)² = 25/9 = 2 7/9
Najlepsza Odpowiedź!
2009-11-21T18:00:54+01:00
1. 3-³ * (1/9)₋³ = 1/3³ * 3⁶= 3³=27
2. 4⁻² * (1/16)⁻² = 1/16 * 256 = 16
3. 5⁻¹ * (1/125)⁻¹ = 1/5 * 125 = 25
4. 6⁻² * (1/36)⁻² = 1/6²* 6⁴ =6²= 36
5. (2/3)⁻² * (3/4)⁻² = 9/4 * 16/9 = 4
6. (1 1/6)⁻³ * (3/7)⁻³ = (7/6*3/7)⁻³=(1/2)⁻³=8
7. (2,8)⁻⁴ * (5/14)⁻⁴ = 1/16 * 1/16 = 1/256
8. -||-
9. (5 1/3)⁻³ * (0,75)⁻³ = (16/3*3/4)⁻³=4⁻³=1/64
10. 3⁻² * 3⁴= 3² = 9
11. 5² * 5⁻⁶ = 5-⁴ = 1/625
12. 4-⁴ * 4² = 4-² = 1/16
13. 2-⁸ * 2₅ = 2-³ = 1/8
14. (1 2/3)¹⁰ * (1 2/3)⁻⁸ = (1 2/3)² = (5/3)² = 25/9 = 2 7/9